Oriented Overgrowths of Poly(l‐Lactide) on Oriented Isotactic Polypropylene: A Sequence of Soft and Hard Epitaxies. Issue 20 (19th July 2018) - Guan, Guangwu; Zhang, Jie; Sun, Xiaoli; Li, Huihui; Yan, Shouke; Lotz, Bernard
Abstract: The crystallization behavior of an amorphous poly(l ‐lactide) (PLLA) layer deposited on uniaxially oriented isotactic polypropylene (iPP) substrate is been studied by atomic force microscopy (AFM) and electron microscopy combined with electron diffraction. A patterned PLLA structure with two fixed lamella and chain orientations is observed. Electron diffraction demonstrates that the major lamellar set is oriented with molecular chains perpendicular to the chain direction of the iPP. The minor lamellar set is inclined at ≈64° to both the iPP chain axis direction and the lamellae of the major set as judged from both the bright field electron micrograph and the AFM image. The orientation of the main set is explained in terms of "soft" epitaxy or graphoepitaxy, in which PLLA chains oriented parallel to the ditches of the iPP substrate caused by alternatively arranged crystalline and amorphous regions. The minor set is due to a homoepitaxy of PLLA with parallelism of the helical paths. The orientation of this minor set of lamellae therefore depends on and can help determine the chirality—l ord —of the PLA investigated. Abstract : The epitaxial crystallization of poly(l ‐lactide) (PLLA) on a highly oriented isotactic polypropylene (iPP) substrate is studied. Two populations of oriented PLLA lamellae are seen edge‐on. For the main set, the lamellae are oriented parallel to the iPP chain direction of the substrate, that is, a perpendicular molecular chain orientation of PLLA with respect to iPP, resulting from a "soft" epitaxy or graphoepitaxy. The lamellae of the minor set are oriented at ≈64° through homoepitaxy of PLLA based on helix–helix interactions (parallelism of interacting helical paths).